8th IET International Conference on Power Electronics, Machines and Drives (PEMD 2016) 2016
DOI: 10.1049/cp.2016.0350
|View full text |Cite
|
Sign up to set email alerts
|

MMC with Parallel-connected MOSFETs for LVDC Distribution Networks

Abstract: A highly efficient DC-AC converter is key to the success of low-voltage DC (LVDC) distribution networks. Calculated power losses in a conventional IGBT 2-level converter, a SiC MOSFET 2-level converter, a Si MOSFET modular multilevel converter (MMC) and a GaN HEMT MMC are compared. Calculations suggest that the parallel-connected Si MOSFET MMC may be the most efficient topology for this LVDC application. In this paper, the current unbalance limits for the parallel-connected MOSFETs and the optimal number of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…1. Previous investigation of the Si MOSFET MMC [11][12][13][14] has shown that conduction losses dominate switching loss due to low effective cell switching frequency. One phase leg of a 3-phase 5-level Si MOSFET MMC converter is shown in Fig.…”
Section: Ac/dc Converters For Ev Chargingmentioning
confidence: 99%
See 4 more Smart Citations
“…1. Previous investigation of the Si MOSFET MMC [11][12][13][14] has shown that conduction losses dominate switching loss due to low effective cell switching frequency. One phase leg of a 3-phase 5-level Si MOSFET MMC converter is shown in Fig.…”
Section: Ac/dc Converters For Ev Chargingmentioning
confidence: 99%
“…The prevalence of conduction losses in MMC makes parallel connection of MOSFETs attractive in order to reduce on-state resistance and hence reduce conduction loss. However, previous studies [11][12][13][14] did not include measured switching losses as Si MOSFET parallel connection was increased, so measured Si MOSFET switching losses will be explored in this paper. In addition, the possibility of reducing EMI using slowed switching was proposed [11], with modelled losses suggesting that switching could be considerably slowed without impacting overall converter loss.…”
Section: Ac/dc Converters For Ev Chargingmentioning
confidence: 99%
See 3 more Smart Citations